KEMAMPUAN MENYIMAK BERITA SISWA KELAS X SMK TELKOM PEKANBARU - Risanti Amelin; Dudung Burhanudin; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This study discusses the ability of Listening News Class X SMK Telkom Pekanbaru. This study was conducted to determine the level of news listening skills class XI student of SMK Telkom Pekanbaru. This study used a technique test the technique in the form of multiple choice objective test. How to measure the level of students' abilities, namely the method of data analysis by giving value to the elements of what, who, why, where, when, and how the news played. Based on the results of the study showed that the overall level of ability to listen to the news element of class X SMK Telkom Pekanbaru classified as moderate with a mean 82, 43. If categorized the ability to listen to the news in determining what elements is high with the average of 89.73. The ability to listen to the news in determining the elements who were moderate with the average of 81.16. The ability to listen to the news in determining why the element is low with the average of 60.18. The ability to listen to the news in determining where the element is high with an average of 85, 26. The ability to listen to the news in determining when the element is classified with a mean of 80, 80. The ability to listen to the news in determining how the element is classified with a mean 84, 91.Keys words: Listening,listening tonews, SMKTelkomPekanbaru